THE INTERPLAY BETWEEN SALES GROWTH AND DIVIDEND POLICY IN ENHANCING FIRM VALUE: THE MODERATING ROLE OF TAX PLANNING - Erlina Widayanti Djatnicka; Tirin Wulandari; Dian Sulistyorini Wulandari (ZILLZELL MEDIA PRIMA, 2025)
This study aims to examine the effect of sales growth and dividend policy on firm value, with tax planning as a moderating variable. The object of the research is manufacturing firms listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. A quantitative approach was employed using panel regression analysis and Moderated Regression Analysis (MRA) to test moderation effects. The results reveal that both sales growth and dividend policy have a significant positive impact on firm value. Furthermore, tax planning significantly moderates the relationship between sales growth and dividend policy on firm value. This implies that firms implementing effective tax planning strategies are better able to enhance the value-creating potential of their operational growth and dividend decisions. The findings offer strategic insights for corporate managers and investors to integrate financial performance indicators with tax efficiency as a means to maximize shareholder wealth.